Disentangling go/no-go from motivational orientation to foods: Approaching is more than just responding. (February 2023) - van Alebeek, Hannah; Veling, Harm; Blechert, Jens
Highlights: The active ingredient in approach-avoidance trainings is probably approach. Approach, but not avoidance modified explicit liking ratings of food cues. Approach, but not avoidance decreased corrugator activity in response to foods. Non-responses on a touchscreen did not devaluate food stimuli. Abstract: Background: Training motor responses to food images can influence subsequent evaluations of the food and even consumption. One important question in the literature is whether training people to approach versus avoid food items is different from training people to respond ('go') versus not responding ('no go') to food items. Therefore, we systematically investigated whether mere action, i.e., withholding responses vs go responses, and motivational orientation, i.e., approach and avoidance, differentially change stimulus valence. Methods: In 60 healthy participants, we contrasted approach, avoidance, and non-responses with the same neutral go response in their potential to change food liking ratings and affective facial responses. Results: Training approach responses to stimuli increased their valence compared to mere go responses to stimuli as was evident from explicit liking ratings and facial corrugator activity. Unexpectedly, not responding to stimuli or avoiding stimuli did not decrease their valence relative to go stimuli. Conclusion: The current results suggest that approach responses may be more effective to increase the valence of food items than mere go responses. They further suggest that the devaluation of non-responded stimuli that is often found in the literature may not become visible in the current task set-up where the Go/No-go training is administered on a touchscreen.